The Transition to a State Medical Service
1942-08 1942 1940s 8 pages area. It may be answered that the boundaries of regions can be adjusted at need, but a region needing continual readjustment had better not exist at all. (14) The excuse for the existing regional administration has been that closer and easier contact with local bodies was essential. We believe that such contact can be better attained by means of the Area Advisory Committees hereinafter referred to, and, possibly, by a certain number of branch offices of the Ministry. In any case, it is to be noted that the 12 regions have not, in fact, made the contacts called for, but have merely interposed a most troublesome delay between the local authority and the Ministry of Health. (D) PROPOSED LOCAL ADMINISTRATION (15) The local administration of health services, even under the complete central control which we advocate, will need offices and personnel sufficient for all routine purposes, both advisory and executive. The wise selection of the type of body to be set up is a matter of the very greatest importance to the future of the public health in this kingdom. There are many models which might be selected, and there will be many claims to have some part in the administration of local services, often enough with the intention of securing fresh opportunities of forwarding particular political creeds, or of securing new spheres for political patronage. (16) We advocate the setting up of statutory bodies to be known as Area Health Committees. These would conform to the administrative type with which we are familiar in the case of National Health Insurance Committees, they would be purely administrative and advisory in function, and without being popularly elected would be so constituted as to secure adequate representation of both local authorities (as representing the general public) and specialised health experience (by nominations from the medical profession, hospital administrators, etc.). (17) Neither the boundaries of Municipal boroughs nor those of administrative counties are, generally speaking, large enough for the purposes of these committees. For example, there are three administrative counties within the boundaries of Lincolnshire, but the whole county, including the boroughs of Lincoln and Grimsby, is by no means too big to form a single Area Health Committee. This example gives some idea of the sort of difficulties which would be encountered and also of the size of unit which we consider appropriate for health purposes. (18) It need hardly be said that county and municipal boroughs would be included in these areas, and would not be allowed to contract out or to administer their own health affairs on an independent basis. (19) The Area Health Committees would necessarily act to a large extent through sub-committees upon which would be co-opted those whose special knowledge might prove of value. (20) The following list of sub-committees which might be found desirable will give some idea of the different spheres in which Area Health Committees will administer the Acts and Regulations decided upon centrally :— (a) General practitioner services, including distribution, numbers, duties, disciplinary machinery, superannuation, promotion, etc. (b) General hospitals, siting, extensions, staff, etc. (c) Special hospitals, such as sanatoria, mental, hydropathic, remedial and accident hospitals, children's hospitals, convalescent hospitals, etc. (d) Nursing. (e) Ambulance and transport. (f) Personnel. (g) Publicity. (21) In the case of Scotland and Wales, these Area Committees would be immediately responsible to national Boards of Health, but these would, in fact, be little more than branches of the Central Ministry with certain delegated powers. It is a matter of opinion whether other branches would be needed, but the Union notes that the Department of Health for Scotland is often independent in a most advantageous manner and believes that the setting up of Western, Midland and Northern Counties branches might be found in practice to help in the initiation of progressive policies. (22) The Area Health Committees would be financed in part by block grants distributed through the Ministry and in part by precepts on the local rating authorities. These authorities would control the expenditure of this rate through their representatives on the Area Health Committee, subject always to their not conflicting with, nor preventing the proper carrying out of, statutory duties under the current Health Plan or other regulations. (E) TAKING OVER THE VOLUNTARY HOSPITALS (23) Much has been said on the text that voluntary and municipal hospitals must enter into a partnership with each other, and both with the State. It appears to be thought that the voluntary hospitals contain some essence or excellence not found in others and too valuable to be lost. It is also argued, often only by inference, that the money contributions made by benevolent persons to the voluntary hospitals are too valuable an asset to be sacrificed, as they might be by nationalisation, or by any but a carefully camouflaged type of State control. (24) The Union neither believes that purely voluntary contributions (without expectation of any return) are significant in amount, nor that voluntary management is anything but wasteful of funds and only too often parochial in outlook. For example, the overpowering benevolence of an individual often compels expenditure on projects which would have had no place in an ordered scheme, while contributory schemes too often secure a priority for their members which is not based on medical needs, the chronic case insusceptible of improvement from hospital treatment is allowed to occupy a bed badly needed for more urgent cases. The Union notes that the Hospital Saving Association is already beginning to be allowed to control the policy of voluntary hospitals to an extent for which its character in no way fits it. 3 292/847/1/4